Targeting the aryl hydrocarbon receptor nuclear translocator complex with DMOG and Stemregenin 1 improves primitive hematopoietic stem cell expansion - Carlo Stephan Jackson; Chrisna Durandt; Ilse Janse van Rensburg; Vincent Praloran; Philippe Brunet de la Grange; Michael Sean Pepper (Stem Cell Research, 2017)
Culture conditions used for the expansion of hematopoietic stem and progenitor cells (HSCs and HPCs, collectively HSPCs) should ideally favor the self renewal of long-term HSCs. At 20% O2, the synthesis of HIF-1α is balanced by its hydroxylation and proteasomal degradation. This favors HSPC differentiation, but can be prevented by culturing CD34+ cord blood cells in the presence of dimethyloxaloylglycine (DMOG). This differentiation may also be reduced by culturing the cells in the presence of Stemregenin 1, an antagonist of the aryl hydrocarbon receptor (AhR). The objective of this study was to investigate how hypoxia, DMOG and Stemregenin 1 might affect the expansion of HSPCs with the aim of identifying optimal conditions for expansion in culture. It was found that DMOG decreased proliferation but was effective in preserving the number of cells in the primitive hematopoietic sub-populations in vitro. The effect of DMOG was similar to hypoxia, although differences were observed with regard to the side population and CD34+ sub-populations. Stemregenin 1 on the other hand increased the size of the primitive as well as the other HSC sub-populations. The use of Stemregenin 1 with DMOG increased the proportion of primitive HSCs to 3.54% compared to 2.61% for Stemregenin 1 alone. In vivo engraftment studies confirmed these findings and showed that fewer cells (3710) are required for long-term engraftment when HSCs are grown in Stemregenin 1 together with hypoxia than in Stemregenin 1 under conditions of normoxia (13430).